Clinical practice with steroid therapy for Duchenne muscular dystrophy: An expert survey in Asia and Oceania - Takeuchi, Fumi; Nakamura, Harumasa; Yonemoto, Naohiro; Komaki, Hirofumi; Rosales, Raymond L.; Kornberg, Andrew J.; Bretag, Allan H.; Dejthevaporn, Charungthai; Goh, Khean Jin; Jong, Yuh-Jyh; Kim, Dae-Seong; Khadilkar, Satish V.; et al. (Elsevier, 2020)
Background: Several studies on clinical practice for Duchenne muscular dystrophy (DMD) have been conducted in Western countries. However, there have been only a few similar studies in Asia and Oceania. Here, we investigate the steroid therapy-related clinical practice for DMD among the local experts. In 2015, we conducted a DMD expert survey in Asia and Oceania to acquire information regarding patients with DMD and to assess current clinical practice with the cooperation of Asian and Oceanian Myology Centre, a neuromuscular disease research network. Results: We obtained survey responses from 87 out of 148 clinicians (62%) from 13 countries and regions. In China, 1385 DMD patients were followed-up by 5 respondent neurologists, and 84% were between 0 and 9 years of age (15% were 10–19 years, 1% > 19 years). While in Japan, 1032 patients were followed-up by 20 clinicians, and the age distribution was similar between the 3 groups (27% were 0–9 years, 35% were 10–19 years, 38% were >19 years). Most respondent clinicians (91%) were aware of DMD standard of care recommendations. Daily prednisolone/prednisone administration was used most frequently at initiation (N = 45, 64%). Inconsistent opinion on steroid therapy after loss of ambulation and medication for bone protection was observed. Conclusions: Rare disease research infrastructures have been underdeveloped in many of Asian and Oceanian countries. In this situation, our results show the snapshots of current medical situation and clinical practice in DMD. For further epidemiological studies, expansion of DMD registries is necessary. © 2020 The Japanese Society of Child Neurology